The Influence Of Health Education On Knowledge Of Free Sexual Behavior - Misrawati T Badudin; Diah Indriastuti; Muhammad Syahwal; Jeyma Sahalul Ordonez (KLASICS, 2022)
Abstract. Sexual behavior in a variety of activities or behavior caused by sexual urges or to get sexual pleasure. Health education regarding free sex behavior is expected to provide knowledge and encourage changes in individual behavior. This study aims to determine the effect of student health education on knowledge about free sex behavior. The study was conducted using pre-experimental methods with the One-Group Pretest-Posttest Design approach. The population, namely all students for the 2019-2020 period, totaled 946 people with a sample size of 90 people who were stabilized by the Cluster Random Sampling technique. The results of statistical tests showed that at the pretest it was known that most of them had good knowledge, namely 62.2%, and in the post-test, good knowledge reached 98.9%. This study shows the effect of health education on knowledge about free sexual behavior (p-value 0.000 <0.05). Knowledge before being given health education about free sex behavior is known to have good knowledge which is 62.2% and less knowledge reaches 27.8%. Most of the knowledge after being given health education about free sex behavior has good knowledge, namely reaching 98.9%. This is because respondents can accept the process of providing health education with an online system that is well accepted.